Hematological Characterization of Hicotea Turtles (Trachemys callirostris [Gray, 1856]) in Córdoba (Colombia) - Carrascal Velásquez, Juan (Universidad de La Salle. Revistas. Revista de Medicina Veterinaria., 2014)
69 samples from Trachemys callirostris were collected in situ and ex situ, to determine their hematological parameters, to compare these values (considering sex, age, and condition), and to establish the morphology of their cells. Blood was collected from the jugular vein of the animals. Hematocrit, hemoglobin concentration, total counts of erythrocytes, leukocytes and thrombocytes, and red cell indices were determined (mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration). Differential leukocyte count was performed, and the morphology of cells found in blood smears was described. The average values found for all individuals were: hematocrit (29.9% ± 5.1), hemoglobin (4.0 ± 1.0 g / dl), MCV (327 ± 15.3 fL), MCH (45 ± 17.5 pg), MCHC (14 ± 6%), total count of thrombocytes (15.0 ± 5.4 × 10³ μL), total count of erythrocytes (0.92 × 10⁶ / μL ± 0.12), and total count of leukocytes (12.10 ± 5.0 × 10³ μL). Analysis of variance showed no statistically significant difference (p < 0.05) between Trachemys callirostris of different weights (500 to 2000 g). Nevertheless, it showed significant (p < 0.05) and highly significant differences (p < 0.01) for most hematologic variables between sexes and hicotea turtles maintained in situ and ex situ. Thus, differences found between individuals, depending on weight, sex and condition of maintenance (in situ or ex situ), serve as a reference to establish protocols for maintaining turtles in captivity.